2023
DOI: 10.3390/ma16113987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Temperature on the Microstructure and Mechanical Properties of CoCrFeNiNb0.2Mo0.2 High Entropy Alloy

Abstract: Strengthening the CoCrFeNi high entropy alloy with a face-center cubic structure has become a research prospect in the last decade. Alloying with double elements, Nb and Mo, is an effective method. In this paper, to further enhance the strength of the Nb and Mo contained high entropy alloy, CoCrFeNiNb0.2Mo0.2 was annealing treated at different temperatures for 24 h. As a result, a new kind of Cr2Nb type nano-scale precipitate with a hexagonal close-packed structure was formed, which is semi-coherent with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…However, the mechanical properties of the alloys, such as compressive strength and fracture toughness, were reduced. Fan et al [10] studied the influence of an annealing treatment at different temperatures for 24 h on a CoCrFeNiNb 0.2 Mo 0.2 high-entropy alloy. It was found that the best mechanical properties were obtained when the annealed temperature was 700 • C.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanical properties of the alloys, such as compressive strength and fracture toughness, were reduced. Fan et al [10] studied the influence of an annealing treatment at different temperatures for 24 h on a CoCrFeNiNb 0.2 Mo 0.2 high-entropy alloy. It was found that the best mechanical properties were obtained when the annealed temperature was 700 • C.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-principal element alloys (MPEAs) are of great interest to researchers because of their high compositional variability and multiple deformation mechanisms, which enable them to have excellent properties, including high strength, wear resistance, and energy storage capability [1][2][3][4][5]. Single-phase face-centered cubic (FCC) high/medium entropy alloys (HEAs/MEAs) have been extensively studied because of their excellent plasticity and good processing properties.…”
Section: Introductionmentioning
confidence: 99%